Profil Penggunaan Antihipertensi pada Pasien Rawat Jalan di Rumah Sakit Ibu dan Anak Pro - Pamudi, Berwi Fazri; Mustika, Ika; Zahira, Mirna Amalya (Jurusan Farmasi, Politeknik Kesehatan Kementerian Kesehatan Aceh, 2024)
Hypertension is one of the biggest causes of death in the world. The results of Riset Kesehatan Dasar in 2018 shows that of the 34 provinces in Indonesia, Aceh Province ranks 27th with a percentage of the population experiencing hypertension of 26.45%. Hypertension is ranked 3rd of the 10 most common diseases at Ibu dan Anak Aceh Hospital. This research aims to determine the profile of anti-hypertensive use in outpatients at the Ibu dan Anak Aceh Hospital for the period January- June 2022. The research method used is descriptive. The population and sample in this study were total prescriptions from outpatients suffering from hypertension who received treatment at Ibu dan Anak Aceh Hospital in the period January - June 2022. The results of the study were based on patient characteristics, the highest number of patients suffering from hypertension were women, 65 people (96%) and the age range most affected by hypertension is 55-64 years old with 21 people (31%). Meanwhile, based on drug characteristics, the most widely used drug class is the Calcium Channel Blocker (CCB) with 108 drug items (43%) and the type of drug most used by hypertension patients is Amlodipine with 99 prescriptions.